Letter (copy)
C02-0083-001 WCS/PD. Dr. H.B. Morgan, Chairman, Spanish Medical Aid Committee, 24 New Oxford Street, W.1. 15th December, 1937. Dear Dr. Morgan, With reference to our discussion on the possibilities of supplying a Bedford de-lousing Van, the body of which can be separated from the chassis, I am enclosing a catalogue from Messrs. Flexion, from whom we can obtain what is termed a "Quick-fit" trailer attachment marked with a red cross on the enclosed catalogue and it is fitted with a van body, zinc lined with all joints soldered and air seals on rear doors, and which to my mind would suit admirably, linked up with the Bedford 2-ton short wheelbase chassis and cab. The question of price is one which at the moment, I can only give approximately and need not exceed £500, but quotations are being obtained for the special body and when these are to hand, I can give you a definite figure. I would confirm that through one of our Traders, we supplied several de-lousing Vans to the Bermondsey Borough Council and if therefore any of your Committee would like to see these, if you would let me know I can no doubt make the necessary arrangements. In regard to the 3-ton Bedford large capacity Van, fitted with 5 k.w. lighting set which should be ready for 292C/946/2/83